Influencing Variables Towards the Intention to Purchase (ITP) and Their Research Gaps - Yaacob, Rohana Binti; Baroto, Mas Bambang (School of Business and Management Institut Teknologi Bandung, 2019)
Abstract. Purchase intention is important to study because research results are frequently used for making decision about product and services and, the research result could predict future sales for organisation. The objective of the research is to define the independent variables which influence the intention to purchase as the dependent variable. The method used in this study was systematic literature review that was supported by articles from prominent journals. The literature review found that there were contradictions in the relationship between variables, such as variables for intention to purchase (trust, price, perceived value and attitude) and technology management to trust, were contradicting on their hypotheses. The study result provided a significant contribution to the academic field like building a conceptual framework for further study in Asian countries context because there are lack research on Asian contexts about all variables in this research. Besides, the contradiction of all linkages between variables will contribute to the body of knowledge.Â Keywords: Â Attitude, intention to purchase, perceived value, price, trust, technology management